Effects of monensin sodium and xylanase in broiler diets - Sylvester, Ethan W.; Delfelder, C.J.; Beyer, R. Scott; Stark, Charles R.; Evans, C.E.; Yoder, Ashton D.; Jones, Cassandra K. (My University, 2017)
Consumer pressure has led to a decrease in the amount of microbial feed additives in broiler diets. Microbial additions to these diets have been implemented to improve feed efficiency and digestibility. A possible replacement for microbial additions in diets is exogeneous xylanase. It is known that xylanase will improve breakdown of fibers in the broiler diets; however, it is unknown if xylanase will be able to replace a common feed microbe, monensin sodium. The objective of this experiment was to examine if xylanase could replace monensin sodium in the feed digestibility of broilers chicks across both corn and wheat based diets. 216 Cobb chicks were fed over the course of 21 days examining the effects of treatments including 16,000 bxu/kg beta 1-4 endo-xylanase enzyme (Econase XT; AB Vista, Marlbough, UK) or 10g/kg monensin sodium (Coban 90; Elanco Animal Health, Greenfield, IN). 6 birds were put in each cage, with the cage as the experimental unit. The diets were designed as a 2×2×2 factorial. The diets were either wheat or corn based with either no additive, only xylanase, or only monensin sodium added. The weight of each cage and feed disappearance were measured weekly over the course of 21 days. Data was then examined utilizing the GLIMMIX procedure of SAS with the fixed effect being the dietary treatment. In the control diets of only corn and wheat, corn improved FCR (P<0.05) when compared to the wheat based diet. Corn with xylanase and monensin sodium diets neither improved the FCR (P>0.05) when compared to the corn control diet. Wheat with monensin sodium did not improve FCR (P>0.05) compared to the wheat control diet; however, xylanase improved FCR (P<0.05) when compared to the control. In conclusion, this trial suggested that corn diet FCR remains unchanged regardless if the diets had either monensin sodium or xylanase. In wheat diets however, this research suggested that by adding xylanase to wheat based diets, the carbohydrate digestion was improved, therefore bringing the FCR of a wheat diet back to that of a corn diet. However, it is noted that there would be a limited impact of an antimicrobial in this setting.
Keywords: Spring 2017